(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The global economic environment is changing rapidly. Developing countries have faced more competition in terms of their exports. In order to be more competitive, each country should develop their business strategies. Small and medium sized enterprises (SMEs) are one of the principal driving forces in economic development. SMEs constitute a major part of the Turkish economy, accounting for a large proportion of the country’s business and total employment. SMEs will be an important power to realize development goals of Turkish economy, and play an important role to take advantage of global environment. For this reason, it is important to pursue the developments of SMEs in Turkey. The purpose of this study is to present an overview of the developments in world markets, relating to SMEs, and assess the SMEs business strategies in Turkey.